Estimating solar radiation according to semi empirical approach of PERRIN DE BRICHAMBAUT: application on several areas with different climate in Algeria - Ghodbane, Mokhtar; Boussad, Boumeddane (جامعة الوادي - university of el oued, 2016)
Tthhee ssoulna.r Teon egregty mreaaxcihmiunmg ae ngeirvgeyn fsruormfa cteh ei ss udnir,e ictt liys dneepceensdsaenryt oan gtohoed o sroielnatra trieocne itvheerr eoorfi eanntda titohne tthoew asurdns's t hpeo ssiotiloanr roavdeira ttiiomne wish ear ev ethrye simolpaorr rtaandti atthioinng i.s T pheer pinentednisciutyla cr atloc uthlae tseo olaf rs ocolallre cratodri,a stioo nth ere kcneoivwelde dbgye aonf ianncdli naesdtr sounrofmaciec ails tdhaet ap roimn-asriyte o bstjuedcyti.v eM oaft ltahbis pwaapse rt.h eT hsei mstuuldayti oisn btaosoeld, ownh tehree taru ep rsooglarar mti mwea, st hde egveeologpraedp htioc cmaoldcuell aotef PthEe RdRaIiNly DglEo bBaRl IsColHarA MraBdAiaUtiTo.n Tchoell escotmede bayp palnicya gtieoongsr aopnh diciaffle rseitnet dpelpaecnesd iinng Aolng ethriea ,s elimkei- eEml-pOiruiceadl, oBbistakrinae, dB wliderae acnodn fiOrmraend ibny tchoem dpaayr inogf tMheamrc hw i2th1 ,t hJeu npere v2i1o,u Ssleyp rteemsubletsr p2u1b laisnhde dD beyc etmheb erer se2a1r, cahnedrs tihse o rf egsruelatst competence in this field.
Article
Keywords: solar energy, global solar radiation, inclined surface, simulation